Intel’s core i7 10th generation (1065G7) Review - Khan, Fahad; Ansari, Mohd Faiz; Nadeem, Mansoori Mohd; Shaikh, Shakila; Pappu, Shiburaj (International Journal of Computer Sciences and Engineering, 2019)
In this research paper, we will look at the Intel’s latest processor (1065G7). We will also deeply study the improvements and enhancement that have been introduced in his processors. For this I have gone through several papers and articles. We have found that this processor is rather fast and power-efficient and It is a very reliable processor and it is one of the best processors at this price range.